2012
DOI: 10.1063/1.4731733
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear propagation of coherent electromagnetic waves in a dense magnetized plasma

Abstract: We present an investigation of the nonlinear propagation of high-frequency coherent electromagnetic waves in a uniform quantum magnetoplasma. Specifically, we consider nonlinear couplings of right-hand circularly polarized electromagnetic-electron-cyclotron (CPEM-EC) waves with dispersive shear Alfvén (DSA) and dispersive compressional Alfvén (DCA) perturbations in plasmas composed of degenerate electron fluids and non-degenerate ion fluids. Such interactions lead to amplitude modulation of the CPEM-EC wave pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Using (14) and (15) in (5)- (12) and collecting the terms in the lowest order of ε, we get the following first-order evolution equations.…”
Section: Derivation Of the Kdv Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using (14) and (15) in (5)- (12) and collecting the terms in the lowest order of ε, we get the following first-order evolution equations.…”
Section: Derivation Of the Kdv Equationmentioning
confidence: 99%
“…The spin effects are considered as one of the most important properties of quantum plasmas due to great significance of highly magnetised quantum plasmas in the atmospheres of neutron stars [12,13]. Marklund and Brodin [14,15] extended the QMHD model and proposed the spin-1 2 QMHD model for hydrodynamic waves.…”
Section: Introductionmentioning
confidence: 99%
“…rate for all four modes are summarized in tables 1 and 2. Recently, the investigation of dense semi-classical or quantum plasmas has received a considerable attention since the dense degenerate plasma is found in modern science and technology such as nano-plasma, quantum-dot, and quantum-well, etc [22][23][24][25][26][27]. Moreover, the streaming instability has been of a great interest in plasmas since it is shown that the instability condition provides a useful information on the characteristics and properties of the plasma configurations with streaming components [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…where φ 0 is defined by (32) and for a long-wavelength plane wave perturbation in a direction with direction cosines (l ζ , l η , l ξ ), ψ is given by…”
Section: Instability Analysismentioning
confidence: 99%
“…Akbari-Moghanjoughi studied the head-on collision of electron-positron-ion magnetoplasmas [25][26][27][28][29] and quasineutral magnetoplasmas [30,31] with different species and distributions using the extended Poincaré-Lighthill-Kuo reductive perturbation method [25][26][27]29], the conventional extended multi-scales technique [28] and other methods for relativistic and non-relativistic cases. Very recently Shukla et al [32] investigated the nonlinear propagation of high-frequency coherent electromagnetic waves in a uniform quantum magnetoplasma composed of degenerate electron fluid and non-degenerate ion fluid. Mamun et al [33] studied the ion acoustic solitary waves (SWs) in the presence of an external magnetic field for ultra-relativistic degenerate electron-ion plasmas using the reductive perturbation technique.…”
Section: Introductionmentioning
confidence: 99%